If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 6 = -3(2y + 6) Reorder the terms: 6 + -3y = -3(2y + 6) Reorder the terms: 6 + -3y = -3(6 + 2y) 6 + -3y = (6 * -3 + 2y * -3) 6 + -3y = (-18 + -6y) Solving 6 + -3y = -18 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 6 + -3y + 6y = -18 + -6y + 6y Combine like terms: -3y + 6y = 3y 6 + 3y = -18 + -6y + 6y Combine like terms: -6y + 6y = 0 6 + 3y = -18 + 0 6 + 3y = -18 Add '-6' to each side of the equation. 6 + -6 + 3y = -18 + -6 Combine like terms: 6 + -6 = 0 0 + 3y = -18 + -6 3y = -18 + -6 Combine like terms: -18 + -6 = -24 3y = -24 Divide each side by '3'. y = -8 Simplifying y = -8
| 2x-15/7=x+5 | | 5.6-2a+n1.4/1.2=4.5 | | X=99+937 | | x^2+165x-2100=0 | | 4n+2=26 | | x+3=3x+21 | | x^2+159x-2100=0 | | 4z+3z=6z+2 | | 64x^4-25y^2=0 | | 4/7x-12=x | | X=99+396 | | (9x/2)-x+(x/14)-(3/7) | | 7x+6y+4=2x-2y-12 | | 2/3x+8=x+9 | | 4(x-2)=5(-3x+2) | | 2y-0.8=3y | | 9x-15=11+7x | | a(x)=x^3+x^2-4x+6 | | 9-7(4-x)=-26 | | 15-9x=7x+11 | | 18(m+.4)-16=118 | | 16x-5=32x+7 | | 3(r-6)+2=4(r+2)+x | | x^2+15x-1000=0 | | 5/7x=10 | | 2/x=4.4/10 | | 6(t-6)+6t=4(3t+3)-11 | | -29-7= | | 3p^2+18p-12=0 | | -5/9=-10x | | x+3/10=2x-1/4 | | 8x^2=8x^2 |